Penerapan design thinking untuk perancangan aplikasi wisata di Kawasan Wisata Taman Nasional Halimun Salak - Muzija, Akbar; Cholil, Saifur Rohman (Jurnal Ilmiah Teknologi Informasi Asia, 2025)
This study introduces a ticket-and-lodging application for Halimun Salak National Park, built with a Design Thinking-driven UI/UX approach. Although the park ranks among Indonesia’s foremost nature attractions, its existing reservation process remains hampered by an unfriendly booking flow and limited access points. The project followed the five Design Thinking phases—empathize, define, ideate, prototype, and test—to observe visitors, pinpoint their needs, and craft a digital remedy that addresses those needs. Interviews and surveys revealed several obstacles, including confusing menus, slow confirmation, and few payment options. These findings guided the creation of wireframes and interactive prototypes. Prospective visitors then used the prototype, and their comments informed refinements to navigation, visual hierarchy, and support tools such as real-time availability and push notifications. User-satisfaction scores and task-completion times were measured before and after the application’s introduction; results showed marked gains in speed and clarity compared with both the conventional website and on-site counters. The new application streamlines ticket and accommodation reservations through an intuitive interface and traveler-oriented features. This solution is expected to spur tourism growth at Halimun Salak National Park while illustrating how digital platforms can advance Indonesia’s wider tourism sector.